O avanço do atraso: o estado, as parcerias público-privadas e o intra-urbano continuado da RMF - Holanda, Breno Santiago (2021)
The successive regulatory adjustments are, nonetheless, testing new possibilities for expanding the capital appreciation fronts, simultaneously, which transform the necessary instruments so the expanded accumulation can take place. For that reason, it is proposed to reflect the analytical bases on which urban policy can be thought and understand how the capitalist state was/will be reformed to meet the final objective of legitimize and expand the spaces for the reproduction and accumulation of capital. Allied to the main objective is the empirical comprehension of political and urban development aspects of the Metropolitan Region of Fortaleza (RMF) which led to the inclusion of space in the capital appreciation circuits, through the State, mainly under the financial aegis. Aiming at the prerogatives of totality and historicity within the theoretical and empirical framework, the Materialist State Theory was used as an explanatory theory of nature, development and state action that also understood the need for capitalist accumulation over space. By understanding Public-Private Partnerships (PPPs) as an indicator of this process, we sought to establish what would become a general overview of the effectiveness of that instrument based on the systematization of news, laws and regulations, which were geospatialized and organized in summary charts. The argument starts from the assertion that PPPs became a central mechanism for spreading the introduction of the neoliberal agenda in public administration, being the result of the agenda preached by Multilateral Organisms, by large national banks and by the dispute for resources after 1988. With them, the public power diversifies the way it acts together with the market, especially with the real estate market. The feeble autonomy of the municipalities precludes investments in infrastructure and imposes a logic of making PPPs effective. In a context that is already marked by the dominance of the formal real estate market in the constitution of its relations and in urban structuring through the segregation and fragmentation of space, these processes feed back into these socio-spatial dynamics.